THE STABILITY OF CARBONATE UNDER UPPER-MANTLE CONDITIONS AS A FUNCTION OF TEMPERATURE AND OXYGEN FUGACITY - Dalton, J; Wood, B (1995)
The stability of carbonate in the upper-mantle is a function of oxygen fugacity. Carbon-carbonate buffers such as EMOG (enstatite-magnesite-olivine-graphite) provide a lower fO2 limit for carbonate stability. For mantle compositions, the position of the carbonate-oxide equilibrium has been experimentally calibrated at 20 kbar and 1000°C at graphite saturation. This equilibrium constrains the upper fO2 limit for carbonate stability given that Fe contents are much less than Mg in both carbonate and spinel. The experimental results are in good agreement with calculations based on existing thermodynamic data. Using appropriate upper-mantle compositions and activity models for carbonate and spinel, it is thus possible, at any pressure, to constrain the stability field of carbonate as a function of temperature and oxygen fugacity. The calculated stability field is generally compatible with current estimates of upper-mantle fO2 (FMQ ± 1.5 log units). -from Authors